286 GASTRIC ELECTRICAL STIMULATION AND SACRAL ELECTRICAL STIMULATION: ARE TWO DEVICES BETTER THAN ONE?. (1st January 2005) - Jain, S.; Al-Juburi, A.; Brizzolora, J.; Secrest, C. L.; Abell, T. L.
Abstract : Introduction: Gastric electrical stimulation (GES) is available as a humanitarian use device for patients with the symptoms of gastroparesis and is effective in reducing gastrointestinal symptoms. We have previously shown that patients with gastric motor disorders often have coexisting abnormalities of the genitourinary system (Gastroenterology 1997;112:A737), which may now be treated with sacral electrical stimulation (SES), resulting in similar improvements in genitourinary symptoms. Patients: We compared the results of therapy with GES and SES in 8 patients who were implanted with both devices. Patients were 6 F, 2 M, mean age of 41 years, who had documented gastroparesis as well as bladder or other pelvic floor dysfunction. All 8 patients had received their GES before the SES. Methods: Patients were evaluated at baseline and latest follow-up (median 4 years for GES and 2 years for SES), according to previously standardized scores of GI (GI: 0-4, TSS max 20) and GU (GU: 0-3, UTSS, max 12) function. Results were compared by paired t-tests and reported as mean ± SE. Results: All 8 patients improved both GI and GU symptoms (see table below) and the results of most parameters as nausea, vomiting, gastric total symptom score (TSS), leakage, voiding difficulty and urinary total symptom score (UTSS) were statistically significant. Conclusions: The combination of GES and SES appears to be both safe and effective for patients with concomitant gastroparesis and bladder dysfunction and the existence of a stimulator for one disorder does not preclude another stimulator.